(untitled) - Munsterberg, Hugo (Rutland, 1962)
the book comes at a time when there is an awakened interest in Oriental art throughout the world. At the same time new methods of art research have been so expanded and refined that many interpretations of earlier writers have been made obsolete.
Keywords: Art; History; Japan